Relationship between Memory Load and Listening Demands in Age-Related Hearing Impairment. (4th June 2021) - Pauquet, Julia; Thiel, Christiane M.; Mathys, Christian; Rosemann, Stephanie
Abstract : Age-related hearing loss has been associated with increased recruitment of frontal brain areas during speech perception to compensate for the decline in auditory input. This additional recruitment may bind resources otherwise needed for understanding speech. However, it is unknown how increased demands on listening interact with increasing cognitive demands when processing speech in age-related hearing loss. The current study used a full-sentence working memory task manipulating demands on working memory and listening and studied untreated mild to moderate hard of hearing (n = 20 ) and normal-hearing age-matched participants (n = 19 ) with functional MRI. On the behavioral level, we found a significant interaction of memory load and listening condition; this was, however, similar for both groups. Under low, but not high memory load, listening condition significantly influenced task performance. Similarly, under easy but not difficult listening conditions, memory load had a significant effect on task performance. On the neural level, as measured by the BOLD response, we found increased responses under high compared to low memory load conditions in the left supramarginal gyrus, left middle frontal gyrus, and left supplementary motor cortex regardless of hearing ability. Furthermore, we found increased responses in the bilateral superior temporal gyri under easy compared to difficult listening conditions. We found no group differences nor interactions of group with memory load or listening condition. This suggests that memory load and listening condition interacted on a behavioral level, however, only the increased memory load was reflected in increased BOLD responses in frontal and parietal brain regions. Hence, when evaluating listening abilities in elderly participants, memory load should be considered as it might interfere with the assessed performance. We could not find any further evidence that BOLD responses for the different memory and listening conditions are affected by mild to moderate age-related hearing loss.